Effects of bone marrow mesenchymal stromal cells-derived therapies for experimental traumatic brain injury： A meta-analysis - Chunli Chen; Cuiying Peng; Zhiping Hu; Lite Ge (Heliyon, 2024)
Background: Bone-marrow-derived mesenchymal stromal (stem) cells [also called MSC(M)] and their extracellular vesicles (EVs) are considered a potentially innovative form of therapy for traumatic brain injury (TBI). Nevertheless, their application to TBI particularly remains preclinical, and the effects of these cells remain unclear and controversial. Therefore, an updated meta-analysis of preclinical studies is necessary to assess the effectiveness of MSC(M) and MSC(M) derived EVs in clinical trials. Methods: The following databases were searched (to December 2022): PubMed, Web of Science, and Embase. In this study, we measured functional outcomes based on the modified neurological severity score (mNSS), cognitive outcomes based on the Morris water maze (MWM), and histopathological outcomes based on lesion volume. A random effects meta-analysis was conducted to evaluate the effect of mNSS, MWM, and lesion volume. Results: A total of 2163 unique records were identified from our search, with Fifty-five full-text articles satisfying inclusion criteria. A mean score of 5.75 was assigned to the studies’ quality scores, ranging from 4 to 7. MSC(M) and MSC(M) derived EVs had an overall positive effect on the mNSS score and MWM with SMDs −2.57 (95 % CI -3.26; −1.88; p < 0.01) and - 2.98 (95 % CI -4.21; −1.70; p < 0.01), respectively. As well, MSC(M) derived EVs were effective in reducing lesion volume by an SMD of - 0.80 (95 % CI -1.20; −0.40; p < 0.01). It was observed that there was significant variation among the studies, but further analyses could not determine the cause of this heterogeneity. Conclusions: MSC(M) and MSC(M) derived EVs are promising treatments for TBI in pre-clinical studies, and translation to the clinical domain appears warranted. Besides, large-scale trials in animals and humans are required to support further research due to the limited sample size of MSC(M) derived EVs.